2020
DOI: 10.1088/1367-2630/abc601
|View full text |Cite
|
Sign up to set email alerts
|

Mesoscopic quantum superposition states of weakly-coupled matter-wave solitons

Abstract: The Josephson junctions (JJs) are at the heart of modern quantum technologies and metrology. In this work we establish quantum features of an atomic soliton Josephson junction (SJJ) device, which consists of two weakly-coupled condensates with negative scattering length. The condensates are trapped in a doublewell potential and elongated in one dimension. Starting with classical field theory we map for the first time a two-soliton problem onto the effective two-mode Hamiltonian and perform a second quantizatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 96 publications
(203 reference statements)
0
17
0
Order By: Relevance
“…From the experimental point of view, the recent BEC soliton experiments with lithium condensates demonstrated that collisions may be recognized as one of the most detrimental effects 34 . However, as we established in 37 , the three-body and one-body losses may be unimportant at the time scales of few tens of milliseconds, which is relevant to experimental conditions in 34 . Moreover, the purely quantum analysis of the problem demonstrated that the superposition of Fock states, occurring at some specific parameters of the system, behaves robust to few particle losses.…”
Section: Discussionmentioning
confidence: 76%
See 4 more Smart Citations
“…From the experimental point of view, the recent BEC soliton experiments with lithium condensates demonstrated that collisions may be recognized as one of the most detrimental effects 34 . However, as we established in 37 , the three-body and one-body losses may be unimportant at the time scales of few tens of milliseconds, which is relevant to experimental conditions in 34 . Moreover, the purely quantum analysis of the problem demonstrated that the superposition of Fock states, occurring at some specific parameters of the system, behaves robust to few particle losses.…”
Section: Discussionmentioning
confidence: 76%
“…1. Previously, in 37 , we examined this problem for quantum solitons possessing simple Josephson coupling. From the experimental point of view, the recent BEC soliton experiments with lithium condensates demonstrated that collisions may be recognized as one of the most detrimental effects 34 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations